Re-purposing of clinical waste : human adipose tissue-derived extracellular matrix as wound dressing material - Cheam, Nicole Mein Ji (2019)
A wound dressing is often needed to aid the wound healing process to enable the wound to close as quickly as possible and the skin to regain its flexibility and strength which are the two primary goals for the treatment of wound healing. Type I collagen is a common material for wound dressings as it is the most abundant protein in humans and has the ability to promote cell behaviour. However, collagen alone is not substantial for wound healing and does not prevent the formation of scars. In recent years, the extracellular matrix (ECM) has received significant attention to be used as a scaffolding material as it consists of a complex 3D architecture structure made up of largely collagen fibres and proteins (i.e. fibronectin, laminin) enabling it to have good bioinductive and biomechanical properties. In this thesis, human adipose tissue, a clinical waste was studied to determine if it can be repurposed into a potential wound dressing material. Human adipose tissue has been found to contain the matricellular protein, Angiopoietin-like 4 (ANGPTL4), which has been proven to be advantageous to wound healing as it is able to promote keratinocyte migration to the wound site as well as to enhance angiogenesis, which could further promote the wound healing process. Hence, adipose tissue derived ECM (Ad-ECM) was extracted using a physical decellularization method to obtain a delipidated and decellularized ANGPTL4-enriched ECM. The Ad-ECM was found to contain various essential proteins for wound healing such as collagen type I, III, IV, elastin, fibronectin and laminin after the extraction, without destroying the triple helical structure of collagen. In addition, ANGPTL4 was also found to be retained after the extraction process which shows that the extraction process was mild and efficient. Subsequently, it was shown that Ad-ECM has scar regulating properties as HDFs cultured onto the material were able to suppress myofibroblastic differentiation as seen from the low levels of expression of α-SMA, col1α1 and SPARC, and the morphology of HDFs remain unchanged after treatment with TGF-β1, a potent inducer of fibroblast-to-myofibroblast differentiation. This phenomenon was observed to be due to the interplay of ANGPTL4. Furthermore, collective cell migration and scratch assays carried out using HaCaTs showed that Ad-ECM promotes faster cell migration than Bv Col type I which further substantiates the potential of Ad-ECM as a wound dressing material.